2022
DOI: 10.1001/jamaophthalmol.2022.0632
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Incidence of Retinal Vascular Occlusions After COVID-19 Diagnosis

Abstract: IMPORTANCE COVID-19 is associated with systemic vascular damage; however, the risk posed to the retinal vasculature remains incompletely understood. OBJECTIVE To assess if there is a change in the incidence of retinal vascular occlusions after COVID-19 infection. DESIGN, SETTING, AND PARTICIPANTS This cohort study at an integrated health care organization (Kaiser Permanente Southern California) included patients without a history of retinal vascular occlusion who were diagnosed with COVID-19 infection between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 9 publications
3
42
1
Order By: Relevance
“…Hypoperfusion on arterial spin label was noted across the gray matter cortex, most prominent after severe COVID-19, suggesting microthrombosis ( 45 ). The latter is consistent with a recent report of retinal vein occlusions in PASC ( 85 ).…”
Section: Formulating Hypotheses For Pasc Pathogenesissupporting
confidence: 94%
“…Hypoperfusion on arterial spin label was noted across the gray matter cortex, most prominent after severe COVID-19, suggesting microthrombosis ( 45 ). The latter is consistent with a recent report of retinal vein occlusions in PASC ( 85 ).…”
Section: Formulating Hypotheses For Pasc Pathogenesissupporting
confidence: 94%
“…As described above, most reports regarding retinal vascular occlusions are cases; therefore, their association with COVID-19 remains unclear. Two cohort studies concerning the incidence of retinal vascular occlusions in the COVID-19 period reported different trends [ 71 , 72 ]. One cohort study recently investigated the prevalence of retinal vascular occlusions before and during the COVID-19 pandemic period [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of retinal artery and vein occlusions slightly elevates within 12 weeks after COVID-19. In particular, an episode of COVID-19 within 6 months is a significant high-risk factor for retinal vein occlusion [ 73 , 74 ]. Moreover, COVID-19 exhibits retinal hemorrhage, cotton-wool spots, and dilated retinal arteries and veins [ 75 ].…”
Section: Retinal Artery Occlusionmentioning
confidence: 99%